1997
DOI: 10.1074/jbc.272.30.18766
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a Protease-sensitive Region in Firefly Luciferase Alters Light Emission Properties

Abstract: Luciferase (EC 1.13.12.7) from the North American firefly, Photinus pyralis, is widely used as a reporter enzyme in cell biology. One of its distinctive properties is a pronounced susceptibility to proteolytic degradation that causes luciferase to have a very short intracellular half-life. To define the structural basis for this behavior and possibly facilitate the design of more stable forms of luciferase, limited proteolysis studies were undertaken using trypsin and chymotrypsin to identify regions of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 17 publications
(20 reference statements)
2
43
0
Order By: Relevance
“…Thermal denaturation assays of FLuc in the presence of PTC124-AMP show a large ΔT m of nearly 30°C, significantly greater than the sum of the ΔT m values for PTC124 and ATP at the same concentration, suggesting that the formation of the adduct is essential for the observed increase in protein stability. Analogs containing nonreactive acid isosteres at the meta position (3)(4)(5), and carboxylate-containing regioisomers at the ortho (10) or para (7) positions, also have significantly reduced thermal shifts, further indicating that FLuc protein stability is dependent on PTC124-AMP formation.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thermal denaturation assays of FLuc in the presence of PTC124-AMP show a large ΔT m of nearly 30°C, significantly greater than the sum of the ΔT m values for PTC124 and ATP at the same concentration, suggesting that the formation of the adduct is essential for the observed increase in protein stability. Analogs containing nonreactive acid isosteres at the meta position (3)(4)(5), and carboxylate-containing regioisomers at the ortho (10) or para (7) positions, also have significantly reduced thermal shifts, further indicating that FLuc protein stability is dependent on PTC124-AMP formation.…”
Section: Discussionmentioning
confidence: 95%
“…Although ideal for following dynamic responses in cell-based assays, reporter instability can be offset by ligand-induced stabilization. Stabilization of FLuc by compounds acting as inhibitors can lead to a relative increase in enzyme levels (compared to untreated basal levels) and correspondingly increased FLuc activity-a counterintuitive result for compounds characterized as FLuc inhibitors (5)(6)(7)(8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is especially pronounced at high temperatures when partial enzyme unfolding leads to the higher accessibility of proteolytic sites (Frydman, 1999). Two protease sensitive regions (206-220 and 329-341 residues) were identified in P. pyralis luciferase amino acid sequence (Thompson et al, 1997). Half-life of luciferase activity in vivo in mammalian cells is only 3-4 hours at 37°C (Leclerc et al, 2000;Thompson et al, 1991).…”
Section: Stability Of Firefly Luciferases In Solutionmentioning
confidence: 99%
“…A majority of the conserved residues are clustered on the surfaces of the two domains opposite each other, suggesting this as a probable location of the active site. It was proposed that a peptide (244HHGF247) obtained through photo-inactivation by 2-(4-benzoylphenyl)-thiazole-4-carboxylic acid (BPTC), a luciferin analogue, may be located at or near the luciferin-binding site [8]. It was subsequently reported that luciferase His-245 mutants showed extremely low specific activity, suggesting that the histidine residue plays a critical role in the active site [9].…”
Section: : T[sg]-s[g]-g-[st]-t[se]-g[s]-x-p[m]-k-g[lf] Motif 2 : Y[lwmentioning
confidence: 99%